2008
DOI: 10.1002/fld.1724
|View full text |Cite
|
Sign up to set email alerts
|

Variance‐reduced Monte Carlo solutions of the Boltzmann equation for low‐speed gas flows: A discontinuous Galerkin formulation

Abstract: SUMMARYWe present and discuss an efficient, high-order numerical solution method for solving the Boltzmann equation for low-speed dilute gas flows. The method's major ingredient is a new Monte Carlo technique for evaluating the weak form of the collision integral necessary for the discontinuous Galerkin formulation used here. The Monte Carlo technique extends the variance reduction ideas first presented in Baker and Hadjiconstantinou (Phys. Fluids 2005; 17, art. no. 051703) and makes evaluation of the weak for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…It originates from the LVDSMC class of methods 30,31,[48][49][50][51][52] for simulating the Boltzmann transport equation. LVDSMC methods achieve computational efficiency 26,27,53 by simulating only the deviation from a suitably chosen equilibrium distribution. For phonon systems, this is given by n…”
Section: Introductionmentioning
confidence: 99%
“…It originates from the LVDSMC class of methods 30,31,[48][49][50][51][52] for simulating the Boltzmann transport equation. LVDSMC methods achieve computational efficiency 26,27,53 by simulating only the deviation from a suitably chosen equilibrium distribution. For phonon systems, this is given by n…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the lattice Boltzmann method (LBM) has experienced remarkable advances and has been developed into a widely used method for simulation of various fluid dynamics phenomena such as, open channel flows [14], low speed gas flows [15], shallow water flows [16], nanofluids [17], solidification [18,19], and so on [20,21]. Unlike conventional CFD methods based on the discretization of macroscopic continuum equations, the main goal of LBM is based on the microscopic models and mesoscopic kinetic equations in which the combined behavior of the particles is applied to simulate the physical mechanism of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this limitation, variance reduction approaches have recently received considerable attention: Baker and Hadjiconstantinou [4] recently showed that solving for the deviation from equilibrium drastically reduces statistical uncertainty and thus enables the simulation of arbitrarily small deviations from equilibrium. The same authors also showed that variance-reduced formulations can be developed for both particle methods [5] and PDE-type approaches [4,6]; a particle method that is equivalent to the one detailed in [5] has also been proposed by Chun and Koch [11]. Unfortunately, in these particle methods, particle cancellation in the collision dominated regime is required for stability [5,11]; this adversely affects both accuracy and efficiency.…”
Section: Introductionmentioning
confidence: 99%